PMA650 : Printing process control / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course is intended to guide and help the student to understand an important of process and quality control aspects in offset lithography. It is important to understand and consider process control not as prepress, plate making and printing, but as an integrated process which can only be successful if there is good communication and control at each stage of the process. To be able to specify and control effectively, the students must understand some of the fundamental principles related to our ability to actually see color. They should understand the principles and theory of color reproduction in offset lithography, plate making procedures and pressrun operation. The element of measurement also will be an important procedure in order to get a good quality in offset lithography operation. Students also will learn how to use a standard and specification for the process control.